Etiology of Diarrhoea with Reference to Multiple Drug Resistant Enteric Bacterial Pathogens - Shrestha, Sirjana Devi; Malla, Sarala; Basnyat, Shital Raj (Nepal Journal of Science and Technology, 2010)
A total of 340 stool samples were processed and studied from both sexes including all ages of patients. Association of enteropathogens between male and female was not statistically significant. Incidence of diarrhoea (28.23%) as well as prevalence of enteropathogens (34.31%) was found highest in the age group (20-30) years. The highest prevalence of enteropathogens (44.87%) was found in August. Of the total isolated enteropathogens, Vibrio cholerae O1 was observed in 51.96% followed by Shigella (18.6%) and Salmonella (8.82%) and parasites were also detected from 20.58% samples. All isolated V. cholerae O1 were El Tor, Inaba. Among Shigella, majority of isolates were S. flexneri. Among Salmonella, S. typhi, S. typhimurium and Salmonella spp. (polyvalent A-S positive) were identified. Entamoeba histolytica, Girdia lamblia, Ascaris lumbricoides and Trichuris trichiura were isolated among parasites. All isolated (100%) V. cholerae O1 were resistant to nalidixic acid and cotrimoxazole, whereas 68%; 63%; 53%; 37% and 11% Shigella were resistant to nalidixic acid, ampicillin, cotrimoxazol, mecillinam and ciprofloxacin respectively. Similarly, 55.5%; 44.4% and 11.1% Salmonella were resistant to nalidixic acid; ampicillin and cotrimoxazole respectively. All V. cholerae strains, 10 strains of Shigella and 2 strains of Salmonella were found multi drug resistant (MDR). The clinical history of the positive cases revealed that abdominal pain, fever, vomiting, dehydration and nausea were the symptoms of enteric infection. Key words: antibiotics; isolates; enteropathogen; Inaba DOI: 10.3126/njst.v9i0.3176 Nepal Journal of Science and Technology 9 (2008) 131-138